2022
DOI: 10.7717/peerj.13884
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic analysis ofBromus(Poaceae: Pooideae: Bromeae) based on nuclear ribosomal and plastid data, with a focus onBromussect.Bromus

Abstract: To investigate phylogenetic relationships among and within major lineages of Bromus, with focus on Bromus sect. Bromus, we analyzed DNA sequences from two nuclear ribosomal (ITS, ETS) and two plastid (rpl32-trnLUAG, matK) regions. We sampled 103 ingroup accessions representing 26 taxa of B. section Bromus and 15 species of other Bromus sections. Our analyses confirm the monophyly of Bromus s.l. and identify incongruence between nuclear ribosomal and plastid data partitions for relationships within and among ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 116 publications
(213 reference statements)
1
4
0
1
Order By: Relevance
“…The trees and networks based on trnL presented large groups formed by many different species, with B. erectus and B. picoeuropeanus found in the section Bromopsis group. These results are similar to those of Nasiri et al [ 51 ], who used a similar methodology to study the phylogenetic relationship within sect. Bromus and determined that neither the ITS nor the plastid markers were capable of discriminating at the species level, while the combination of ITS and ETS allowed them to be discriminated at species level.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The trees and networks based on trnL presented large groups formed by many different species, with B. erectus and B. picoeuropeanus found in the section Bromopsis group. These results are similar to those of Nasiri et al [ 51 ], who used a similar methodology to study the phylogenetic relationship within sect. Bromus and determined that neither the ITS nor the plastid markers were capable of discriminating at the species level, while the combination of ITS and ETS allowed them to be discriminated at species level.…”
Section: Discussionsupporting
confidence: 90%
“…Since previous molecular studies have revealed that the section Bropmosis , in which B. picoeuropeanus was classified by Rico and Acedo [ 54 ], is polyphyletic e.g., [ 14 , 51 ], sequences from different Bromus sections generated in previous studies were included in the analyses. The newly generated sequences together with Bromus sequences from previous studies available at GenBank (see Table S1 ) were used to generate several datasets: the ITS dataset, ETS dataset, trnL dataset, nuclear dataset, and the combined dataset.…”
Section: Methodsmentioning
confidence: 99%
“…B. inermis , B. benekenii , and B. riparius , which all belong to Bromopsis , constitute several independent lineages and are not clustered into a single clade, which is in agreement with the results of Saarela and Pillay [ 13 , 14 ]. Nasiri [ 1 ] found that Bromeae sect. Genea is not monophyletic in plastid trees.…”
Section: Discussionmentioning
confidence: 99%
“…Pillay [ 13 ] analyzed the enzyme cleavage sites of Bromus using phylogenetic information and obtained a simple phylogenetic chart, which provided a preliminary analysis of the genetic relationships of Bromus . Saarela and Nasiri [ 1 , 14 ] confirmed the monophyletic nature of Bromus . However, the ribosomal and cp data were inconsistent for the Bromus major lineage.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation